PENUNDAAN PRESTASI PELAKSANAAN KONTRAK BISNIS DISEBABKAN PANDEMI COVID SEBAGAI DASAR FORCE MAJEURE (Lex Jurnalica, 2021)
In a contractual relationship, each party who agrees to an agreement must carry out all the provisions contained in the agreement. If the contract made by the parties does not include a force majeure clause as the reason for the parties to postpone the performance, and what if the parties who make the contract do not include an epidemic of disease outbreaks as part of the force majeure situation, can the agreement be cancelled. The research method used is a normative research method. The approach method used in this research is the statutory approach and the conceptual approach. The determination of COVID-19 as a national disaster cannot be used as a reason for force majeure to occur. The existence of a causality or cause-and-effect relationship to the determination of COVID-19 as a national disaster on the implementation of the agreement is important to be studied to determine the force majeure situation, in relation to proving the element of "an unexpected thing causes the parties to be unable to carry out theirobligations". In determining the existence of a causal relationship, it is important to determine the extent to which the agreement cannot be implemented. Whether the achievements in the agreement can not be fulfilled as a whole or only partially. Keywords: Force Majeure, Agreement